Dynamics of noncontact rack-and-pinion device subject to thermal noise: Multiharmonic motion of the rack - Dehyadegari, Amin; Miri, MirFaez; Etesami, Zahra (International journal of non-linear mechanics, 2017)
We study miniaturized noncontact rack and pinion composed of a corrugated plate and a corrugated cylinder intermeshed via the lateral Casimir force. We assume that the rack position versus time is a periodic multi-harmonic signal. The axle of the pinion is subject to Casimir torque, frictional torque, load torque, and random Gaussian torque. A Fokker-Planck rather than Langevin description of the pinion dynamics allows us to explore a huge parameter space in a reasonable computational time. We show that even at the room temperature, the device acts as a mechanical rectifier: The pinion rotates with a nonzero average velocity and lifts up an external load. For typical values of parameters, we find that the pinion rotates with an average angular velocity ∼1−30Hz. The thermal noise may even facilitate the device operation. •The noncontact rack and pinion intermeshed by the lateral Casimir force, is studied.•The Casimir device rectifies multiharmonic motion of the rack.•The Casimir rectifier is immune to the thermal noise.